If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 6(-6 + -4x) = 92 4 + (-6 * 6 + -4x * 6) = 92 4 + (-36 + -24x) = 92 Combine like terms: 4 + -36 = -32 -32 + -24x = 92 Solving -32 + -24x = 92 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -24x = 92 + 32 Combine like terms: -32 + 32 = 0 0 + -24x = 92 + 32 -24x = 92 + 32 Combine like terms: 92 + 32 = 124 -24x = 124 Divide each side by '-24'. x = -5.166666667 Simplifying x = -5.166666667
| 3c=c+44 | | 15.12(x-5)=30 | | 19w-45=4w | | 9y-7=8y | | 3x+5x-2x+18=42 | | x+2(3)=2 | | x(0.06)=6996-x | | 3u-19=2u | | y=(-x^3)+6x | | y=2x^4-10x^2+6x | | 12z+9=10z+19 | | X(10x+29)+21=0 | | c+5=6c | | 5(2v+-4)+-2(3v+2)=-4 | | 10q-11=8q+9 | | -4[x-11]=16 | | (3-K)/8=-8 | | Logbase(x+1)64=3 | | 5(2y-4)-2(3v+2)=-4 | | w-18=10 | | y=3x^5-3x+5 | | Pv=2nv-5p | | 1.5p=50 | | 4b=b+15 | | -7=-1-3p | | u+3=4u | | 5/6-13/30 | | f(x)=(x+4)(x-1)(x-1) | | 296+29=(x-24) | | 4x=-156 | | y+16=5y | | y=4x^3-2x^2-7x+3 |